PENGARUH E-WOM TERHADAP CITRA DESTINASI, KEPUASAN DAN LOYALITAS (Studi pada kunjungan wisatawan di DIY) - Sang Putu Angga Mahendra Putra (Modus, 2017)
The tourist loyalty to a tourist attraction is an important thing to be improved. The increasing of loyalty can be done by creating the satisfaction and image of a good destination. Loyalty is also influenced by how strong the consumer is willing to do word of mouth.This research was conducted in Yogyakarta, which is 150 tourists who visited Yogyakarta tourism object and the surrounding area. The objective of this research is to know the role of satisfaction and image of tourist destination on the influence of ¬e-wom to the loyalty of tourists. Sampling method used is purposive sampling. The analytical method used is path analysis.The results provide information that the image of the destination mediates the influence of e-wom on the satisfaction of tourists, the image of the destination mediates the influence of e-wom on tourist loyalty, the satisfaction mediates some e-wom influences on tourist loyalty, and the satisfaction mediates some influence of destination image on tourist loyalty.Keywords: e-wom, destination image, loyalty satisfaction.